A surround display warp-mesh utility to enhance player engagement - Henden, C.; Champion, Erik; Muhlberger, R.; Jacobson, J. (2008)
Surround displays are used in simulation, training, and other applications based on virtual worlds. A wide-view display engages the viewer's peripheral vision, providing a more accurate view of the virtual world and therefore a heightened sense of immersion. However, most commercially available surround displays are expensive and complex. We developed a low-cost alternative, which uses a standard digital projector, a hemispherical mirror, and any roughly spherical or cylindrical screen. The software can handle irregular surfaces and will be open-sourced in the next release of the CaveUT/VRGL freeware. We also conducted a pilot study comparing game play in our prototype and game play with a standard desktop monitor. Players using the surround display reported significantly shorter (P = 0.0051) perceived duration of time during play. Reduced awareness of the passage of time during game play was positively correlated with greater engagement and enjoyment © 2009 Springer Berlin Heidelberg.